2009
DOI: 10.4269/ajtmh.2009.08-0637
|View full text |Cite
|
Sign up to set email alerts
|

Severe Imported Malaria in Adults: Retrospective Study of 20 Cases

Abstract: Abstract. Severe imported malaria is an important problem in many countries in which this disease is not endemic. This retrospective study describes the characteristics of 20 adults with severe imported malaria admitted to our intensive care unit from 1991 through 2007. All episodes were caused by Plasmodium falciparum and all patients had returned from sub-Saharan Africa, except for one transfusion recipient. All persons were considered non-immune, and none had taken appropriate chemoprophylaxis. The median t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
20
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 19 publications
1
20
0
2
Order By: Relevance
“…In reports describing malaria at ICU facilities in high-income countries, bacterial coinfections were detected in 24 to 30% of critically ill patients (11,12) and fatal cases (28). In one study, bacteremia was detected in 4.5% of ICU-treated malaria patients; however, 8 of these 18 cases were nosocomial infections (12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In reports describing malaria at ICU facilities in high-income countries, bacterial coinfections were detected in 24 to 30% of critically ill patients (11,12) and fatal cases (28). In one study, bacteremia was detected in 4.5% of ICU-treated malaria patients; however, 8 of these 18 cases were nosocomial infections (12).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of bacterial infections in travelers with malaria can therefore be highly informative since there is little risk of diagnostic misclassification. Although stated in a few reports from intensive care units (ICUs) (11,12), the frequency of bacterial coinfections has not been systematically assessed in travelers with malaria.…”
mentioning
confidence: 99%
“…We assume that the patients' age distribution is a consequence of professional migration trends. Average symptom duration prior to hospital admission was approximately seven days (longer in severe cases), a fact observed by other authors [20,21]. Symptoms were often attributed to other, mundane diseases, and/or were intentionally disregarded by both patients and physicians.…”
Section: Discussionmentioning
confidence: 64%
“…Haemoglobinuria (also called blackwater fever) and disseminated intravascular coagulation (DIC) occurred in one patient each. According to research by authors from Germany and Spain, hyperbilirubinemia and hyperparasitemia were most commonly associated severe malaria [21,26]. A multicentric study from Thailand showed that jaundice was present in 529 of 1050 patients (50.4%) with severe malaria and a hyperparasitemia was present in 33.3% [27].…”
Section: Discussionmentioning
confidence: 99%